Government Social Policy: Implementation of The Free Nutritious Meal Program (MBG) - Febri Ananda Dwi K.S; Jamaluddin Jamaluddin; Wulan I.R. Sari; Lira Rachmaliana (FEB Universitas Mulawarman, 2025)
The Free Nutritious Meals Program (MBG) is a flagship policy promoted by President Prabowo Subianto. The MBG has a national strategic goal of reducing stunting and malnutrition rates, which will have an impact on improving Indonesia's human capital. This study aims to uncover dilemmas within the MBG program, examine stakeholder responses, and elucidates the program execution using the Theory of Change (ToC) framework. This research employed a qualitative method utilizing phenomenological approach. The research sites comprised three schools in City A and City B, located in East Kalimantan Province. The informants for this study were students as beneficiaries, school officials involved in MBG management, and the Nutrition Fulfillment Service Unit (SPPG). Findings indicates that the MBG program has succeeded in providing nutritious food according to Recommended Dietary Allowances (AKG), which has had a positive impact on improving students' healthy behavior and concentration. However, obstacles still encountered include delays in distribution, limited menu variety, exclusion of small local suppliers and inadequate monitoring and assessment. This study elucidates systemic dilemmas in governance, the marginalization of small enterprises, and the economic repercussion for school cafetaria vendors